Hydrogel-Based Electrodeposition of Copper Nanoparticles for Selective Detection for Hydrogen Peroxide - Jihun Han; Jihyeon Kim; Byung-Kwon Kim; Kyungsoon Park (Chemosensors, 2023)
A copper-modified indium tin oxide (ITO) electrode was utilized as an electrocatalytic sensing platform for hydrogen peroxide (H2O2) detection. In this study, instead of conventional solution-phase electrodeposition, electrochemical deposition was used to deposit Cu on an ITO electrode with agarose hydrogel. The hydrogel-based Cu nanoparticles exhibited a more evenly dispersed distribution compared to those in the solution phase. Additionally, by incorporating agarose hydrogel as a solid electrolyte, the overall active surface area of Cu nanoparticles on the electrode surface was increased, mainly resulting from a decrease in the aggregation of Cu nanoparticles. Cyclic voltammetry and chronoamperometry confirmed that the resulting Cu nanoparticles possessed distinct electrocatalytic activity for H2O2 reduction and good selectivity for various interfering substances. The chronocoulometry response of the fabricated sensor obtained at −0.6 V (vs. Ag/AgCl) increased linearly with a dynamic range of 1–500 μM, and the limit of detection for H2O2 was 1.73 μM. Our research provides new possibilities for the electrochemical synthesis of metal nanoparticles for non-enzymatic sensing applications.